2010
DOI: 10.1111/j.1365-313x.2009.04061.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protein factors and U3 snoRNAs from a Brassica oleracea RNP complex involved in the processing of pre‐rRNA

Abstract: SUMMARYWe report on the structural characterization of a functional U3 snoRNA ribonucleoprotein complex isolated from Brassica oleracea. The BoU3 snoRNP complex (formerly NF D) binds ribosomal DNA (rDNA), specifically cleaves pre-rRNA at the primary cleavage site in vitro and probably links transcription to early pre-rRNA processing in vivo. Using a proteomic approach we have identified 62 proteins in the purified BoU3 snoRNP fraction, including small RNA associated proteins (Fibrillarin, NOP5/Nop58p, Diskerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…A few snoRNAs have been found to regulate pre-rRNA processing in yeast and animals, but little is known about the function of snoRNAs in planta, with the exception of recent studies of the U3 snoRNP (18)(19)(20)(21). As one of the core components in the small subunit processome, U3 snoRNP has been shown to have a conserved function in 18S rRNA biogenesis (8,17,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few snoRNAs have been found to regulate pre-rRNA processing in yeast and animals, but little is known about the function of snoRNAs in planta, with the exception of recent studies of the U3 snoRNP (18)(19)(20)(21). As one of the core components in the small subunit processome, U3 snoRNP has been shown to have a conserved function in 18S rRNA biogenesis (8,17,23).…”
Section: Discussionmentioning
confidence: 99%
“…The U3 C/D box snoRNP shown to be universally conserved across eukaryotes is the core component of the small subunit processome essential for 18S rRNA processing (16,17). In plants, it has been reported that the U3 snoRNP forms a stable complex with nucleolin protein 1 (NUC1), which binds nascent pre-RNA at the 5′ ETS and specifically cleaves pre-rRNA at the P site (18)(19)(20). Moreover, NUC1-U3 snoRNP binds rDNA before its interaction with prerRNA (20,21).…”
Section: Panmentioning
confidence: 99%
“…Consistent with this, the Arabidopsis ortholog of the mammalian DEAD box helicase (Table I), eIF4A-III, and the putative anchor protein of the exon junction complex (Koroleva et al, 2009;Supplemental Table S1, sheet 3), are among the CML38-interacting proteins detected by MS analysis. In addition, CML38 immunoprecipitates also contained proteins associated with the nuclear U3 snoRNP complex (small and large ribosomal subunit proteins, TCH-1 chaperones, and the 26S proteasome regulatory subunit S2; Table I; Samaha et al, 2010), which is involved in ribosome biogenesis, suggesting another potential function in RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…SG particles consist of mRNA bound in an arrested state as a preinitiation (48S) complex composed of small 40S ribosomal subunits, eIFs, and mRNA-associated proteins like the poly(A)-binding protein (Kedersha et al, 2002;Kimball et al, 2003). Besides these core components, proteomic analyses of SGs reveal that these structures are complex, with a large array of protein components, including RNAprocessing proteins, metabolic enzymes, chaperone proteins, and cell signaling components, associated with the granule complex (Samaha et al, 2010;Isabelle et al, 2012;Sorenson and Bailey-Serres, 2014). Functionally, SGs are proposed to be in dynamic equilibrium with other RNA nucleoprotein particles, such as processing bodies (PB) involved in mRNA degradation, and polysomes involved in mRNA translation.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis also revealed that all elements contain a 13 bp sequence homologous to the hinge structure from A. thaliana U3snoRNA. 20,21 In yeast and animals, U3 hinge sequences base pair with sequences in the 5'ETS and direct sequences revealed the existence of four classes of 45S rDNA genes in A. thaliana (Col0). These can be distinguished from each other by length differences in the 3'ETS, due to the presence of insertions/ deletions just downstream from the predicted RNAseIII cleavage site.…”
Section: Variations On a Teammentioning
confidence: 99%